Keuangan Sosial Islam dalam Tinjuan Maqosid Syariah - Bakhri, Saiful; Firdaus, Salsabila (Tasharruf : Journal of Islamic Economics and Business, 2023)
Islamic economics emerged as part of a larger project of Islamization in the field of economics. The Philanthropy is a concept that already exists in Islam, which aims for good. The effectiveness of philanthropy in efforts to reduce social inequality is inseparable from the role of philanthropic institutions that manage these activities. While the concept of maqasid sharia is the concept of benefit. And realizing benefit is the keyword for humans to recognize what is good for them. The rationale for benefit comes from the Qur'an and al-hadith, which are used by humans to create ijtihad and determine the idealized benefit in their lives and lives. Initially, the discourse on the concept of Maqashid Syariah was a separate sub-topic of the discipline of Ushul fiqh.